2015
DOI: 10.1007/s10531-015-1028-z
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about the effect of patch size on primate species across life history traits?

Abstract: Habitat loss and fragmentation are significant threats for primate species worldwide. However, few attempts have been made to look for general patterns in primate responses to habitat loss and fragmentation, or whether these may be associated with species' traits. We conducted a review of published literature on effects of patch size to quantify the effect of a reduction in this predictor on primates, and to determine whether these effects depend on species' traits. The effects of patch size on seven response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 78 publications
0
16
0
1
Order By: Relevance
“…It is useful to analyse the determinants which influence home range size and what influences home range sizes between groups in the same habitat [1114]. Patterns of ranging behaviour can be influenced by the distribution and abundance of food trees [15–19], phenology [20,21], body size [22–24], group size [2528], location of night trees [29–35], interaction between conspecific groups [36] and the need to patrol territorial boundaries [3741]. Calculating home range overlap provides information about the area shared between groups, this area represents a shared space where gibbons compete for food resources.…”
Section: Introductionmentioning
confidence: 99%
“…It is useful to analyse the determinants which influence home range size and what influences home range sizes between groups in the same habitat [1114]. Patterns of ranging behaviour can be influenced by the distribution and abundance of food trees [15–19], phenology [20,21], body size [22–24], group size [2528], location of night trees [29–35], interaction between conspecific groups [36] and the need to patrol territorial boundaries [3741]. Calculating home range overlap provides information about the area shared between groups, this area represents a shared space where gibbons compete for food resources.…”
Section: Introductionmentioning
confidence: 99%
“…This sample agrees with the general reported trend that Malagasy taxa respond negatively to anthropogenic habitat change (Gardner, 2009; Knoop et al, 2018). However, the preponderance of confounding factors inherently linked to fragmentation (Ewers & Didham, 2006; Miller‐Rushing et al, 2019) makes it difficult to extricate fragmentation's true impact and to then characterize a general response of lemurs to fragmentation, a challenge that has been emphasized by studies across non‐human primates (Carretero‐Pinzón et al, 2016; Onderdonk & Chapman, 2000). Although every fragmented landscape is unique, the wide variety of fragment metrics employed across examined studies in Madagascar, an unclear distinction between “fragments” and “continuous” forests, and the breadth of tests employed to examine fragmentation's effects, indicate the challenge of working across nonstandardized definitions of fragmentation (Ewers & Didham, 2006; for primates: Arroyo‐Rodríguez et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analytic and pantropical study of the responses of 116 primate species to habitat disturbance revealed an overall decrease in primate biodiversity metrics (e.g., species richness, abundance) in disturbed environments (Almeida‐Rocha et al, 2017). With an increasing number of studies on primates in fragments being published (Arroyo‐Rodríguez & Fahrig, 2014; Marsh & Chapman, 2013) and encouraged (Arroyo‐Rodríguez & Fahrig, 2014; Arroyo‐Rodríguez & Mandujano, 2009), numerous comprehensive reviews have assessed the responses of primates to fragmentation (Benchimol & Peres, 2014; Carretero‐Pinzón, Defler, McAlpine, & Rhodes, 2016), reporting numerous responses to its effects (Arroyo‐Rodríguez et al, 2013). Often no clear species traits predict primate persistence in fragments (Gibbons & Harcourt, 2009; Onderdonk & Chapman, 2000); however, a general trend of decreasing species richness with fragmentation, as defined by fragment area, appears to hold across most primate regions (in Asia, Madagascar, and South America: Gibbons & Harcourt, 2009; Harcourt & Doherty, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Habitat loss and fragmentation are two of the main drivers of primate species declines (Rylands et al 2008a;Schwitzer et al 2015). Although these processes occur at the landscape level, most primate research has been focussed on effects of site and patch scales, with little focus on the landscape scale effects (Arroyo-Rodriguez et al 2013a, Arroyo-Rodriguez & Fahrig 2014, Carretero-Pinzón et al 2015. Therefore, the understanding of the effect of site, patch and landscape variables on primate species' responses to habitat loss and fragmentation is still unclear, but necessary for primate conservation.…”
Section: Effects Of Habitat Loss and Fragmentation On Primatesmentioning
confidence: 99%
“…Most studies have been conducted using the first approach to assess group changes in ecological and behavioural variables comparing one or several groups in small fragments to one or two groups of primates in a larger fragment or continuous forest (Chapman et al 2005a;Arroyo-Rodriguez & Dias 2010;. Although we have information on primate species responses to changes in patch size (Carretero-Pinzón et al 2015), the effect of habitat loss and fragmentation processes at different scale has been done only in a few studies (Thornton et al 2011;Arroyo-Rodriguez et al 2013b). …”
Section: Effects Of Habitat Loss and Fragmentation On Primatesmentioning
confidence: 99%